Long-term storage of kimchi cabbage using ozone-plasma and dynamic controlled atmosphere methods: impacts on kimchi quality and fermentation - Ju Young Lim; Jeong Hyeon Lee; Chun Wan Park; Jin Ju Lee; Sung Gi Min (International Journal of Food Properties)
Seasonal variability in kimchi cabbage presents challenges to the kimchi industry, highlighting the need for advanced storage methods to maintain quality. This study evaluated the effects of ozone-plasma (OP) and dynamic controlled atmosphere (DCA) storage on the quality of kimchi cabbage and their impact on kimchi fermentation. Both OP and DCA significantly reduced trimming losses and preserved the visual quality of kimchi cabbage during storage, with DCA achieving the best results, reducing trimming losses by 52% compared to the control. Microbial community analysis revealed that extended storage increased the relative abundance of Leuconostoc gelidum in kimchi. Notably, kimchi made from cabbage stored for 8 m (OP8K, DCA8K) was dominated by L. gelidum both before and after fermentation, potentially affecting its taste and quality. Metabolite analysis indicated substantial differences in kimchi profiles depending on storage duration, with OP8K and DCA8K showing elevated levels of metabolites associated with organic- and amino acids. These findings suggest that OP and DCA storage methods effectively preserve kimchi cabbage, with DCA offering greater economic benefits due to minimal trimming losses. For optimal kimchi quality, using DCA-stored kimchi cabbage within 5 m is recommended.